Un modelo de diseño interactivo como soporte y ampliación instruccional en la enseñanza de la geometría en la ESO - Josep María Fortuny Aymemí; Jesús Murillo Ramón; José F. Martín Olarte; Daría Trevijano Carpintero (Universidad de La Rioja, 2013)
The paper presents the posings on the design, implementation and validation of one model of interactive design, as support and instructional enlargement in the learning of geometry in the E.S.O., by means of establishement of a communication network that permits the use of mail and electronic panel, inside a new conception of a more opened and communicative training.